Use of biochar from oil palm kernel shells enriched in cow manure biol to improve overgrazed soils - Lozano Reátegui , Ronald Marlon (2021)
The palm oil (Elaeis guineensis) agroindustries in Pucallpa produce as residues, seed shells (cuescos) contaminating the soil; the raising of cattle, originates manure (vacaza), that produces polluting gases; and, the deterioration of soils by overgrazing, are environmental problems that need viable solutions. The present investigation evaluated the improvement of the physicochemical properties of degraded soils by overgrazing, applying biochar made from pyrolysis pits and enriched in cow biol produced by anaerobic fermentation. The methodology comprised a Completely Random Block Design (DBCA) with a control (T0) and three treatments (T1, T2, T3), with 5, 10 and 15 t h-1 of enriched biochar respectively, randomly assigned in triplicate to 16 experimental units of 2.4 m by 5.0 m (12 m2) each, contained in four blocks. Statistical analysis included the Shapiro-Wilks and Levenne test, also Tukey and Friedman. The results for pH, organic matter, apparent density, cation exchange capacity and nitrogen were not significant (p> 0.05), whereas phosphorus with T3 and Potassium with T2 did show a significant difference (p <0.05) , to improve the physicochemical characteristics of overgrazed soils by applying biochar enriched with biol de vacaza.